IMPLEMENTING THE CIRCULAR ECONOMY IN THE TEXTILE AND CLOTHING INDUSTRY: BARRIERS AND OPPORTUNITIES - Figueiredo, Anna Carolina Moraes; Morais, Angélica; Mendes, Francisca Dantas (Seven Editora, 2025)
The circular economy (CE) model has been widely studied by the scientific community as a viable solution to reconcile economic growth with environmental sustainability. What exists today in the textile and clothing area is a model that extracts, manufactures, uses and discards incessantly. Through the analysis of several recent studies, this work intends to analyze what has been produced in the literature to point out the barriers that prevent the implementation of CE in the textile field, as well as the opportunities to execute it. Mistakes in the manufacturing process, design phase, disregard for the extension of product life cycles, as well as the need for collaboration of those involved in the supply chain, as well as the demand for product tracking, are some of the problems diagnosed. As a result, there is the identification of samples of the mistakes that have been causing environmental disasters around the world. After all, clothes and textiles accompany practically all human beings worldwide and their poor disposal has proven devastating. DOI: https://doi.org/10.56238/sevened2024.037-175